Echinoderm abundance and diversity in Divinubo and Punta Maria, Borongan City, Eastern Samar, Philippines - Buna, Roz Ann Faith C.; Verona, Rey T. (2024)
Echinoderm is one of the phyla with high diversity and abundance in the Philippines. However, there is little to no information regarding this group in the Eastern Visayas Region, as compared to the sufficient research projects in southern parts of the country. Hence, an initial baseline survey was conducted to assess the abundance and diversity of echinoderms in the intertidal zones of two chosen barangays in Borongan, Eastern Samar: Divionubo and Punta Maria, A semi-purposive sampling was utilized using the transect-quadrat method. Thirty one (31) echinoderm species belonging to classes Asteroidea, Echinoidea, Holothuroidea, and Ophiuroidea were recorded through morphology-based identification. Most of the identified and classified species were sea cucumbers represented by 14 species from four genera and two families, sea urchins with six species from three genera and two families, and sea stars with four species from four genera and three families. The recorded echinoderms in the sampling areas had moderate diversity and evenness, no dominant species, and mostly exhibited clumped distribution. Furthermore, not sll species were shared by the two communities. The abundance and biodiversity characteristics can be possibly attributed to the prevalence of seagrass beds and rocky areas, which serve as primary habitat and food source of echinoderms. This suggested a positive marine health status, despite the presence of threats such as gleaning activities. The physicochemical parameters fell within normal ranges, suggesting a conducive environment for echinoderms to thrive and propagate. It is recommended to conduct subsequent investigations, particularly focusing on monitoring echinoderm species, to further evaluate the status of these crucial organisms.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Echinoderms -- Science and Technology